Friendly touch increases gratitude by inducing communal feelings - Simão, Cláudia; Seibt, Beate (Frontiers in Psychology, 2015)
Communion among people is easily identifiable. Close friends or relatives frequently touch each other and this physical contact helps identifying the type of relationship they have. We tested whether a friendly touch and benefits elicit the emotion of gratitude given the close link between gratitude and communal relations. In Study 1 we induced a communal mindset and manipulated friendly touch (vs. non-touch) and benefit to female participants by a female confederate. We measured pre- and post-benefit gratitude, communal feelings, and liking towards the toucher, as well as general affect. In Study 2 we manipulated mindset, friendly touch and benefit, and measured the same variables in female pairs (confederate and participants). In both studies the results showed a main effect of touch on pre-benefit gratitude: participants who were touched by the confederate indicated more gratitude than those not touched. Moreover, benefit increased gratitude towards a confederate in the absence of touch, but not in the presence of touch. Additionally, perceiving the relationship as communal, and not merely liking the confederate, or a positive mood mediated the link between touch and gratitude. The results further support a causal model where touch increases communal feelings, which in turn increase gratitude at the end of the interaction, after having received a benefit from the interaction partner. These results support a broader definition of gratitude as an emotion embodied in communal relationship cues.